Class Experiences with Inquiry Learning Spaces in Go-Lab in African Secondary Schools - Fer Coenders; Nuno Gomes; Rola Sayegh; Isaac Kinyanjui; Aurelle Noutahi; Nissi Madu (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2020)
Inquiry Based Learning (IBL) is a form of active learning, often used in STEM education to promote conceptual learning and to acquire scientific investigation skills. This paper reports on a study in which teachers in Kenya, Nigeria and the Republic of Benin implemented IBL embedded in online and offline Inquiry Learning Spaces (ILS) in their classes using the Go-Lab platform (https://www.golabs.eu). After a brief description of the IBL methodology, of lab work and in particular virtual labs for STEM education, of the process of preparing teachers to use IBL in class, and of the context of this study, we highlight the methodology used, and finally report our results. These show that the introduction and class enactment of a digital inquiry based learning platform such as Go-Lab in Africa (i) is possible, although challenging, (ii) does lead to student learning, (iii) for this to take place teacher training is necessary, (iv) the digital infrastructure is present in the schools though minimal and fragile, and (v) a local partner needs to provide assistance when required.